REMOTE SENSING OF LAKE SEVAN WATER SURFACE TEMPERATURE USING COPERNICUS GLOBAL LAND SERVICE DATA (Proceedings of the YSU C: Geological and Geographical Sciences, 2023)
Water surface temperature is an important factor influencing the ecological state of the lake. Remote sensing techniques are an important tool for obtaining lake surface water temperature, which provides periodic information from the entire surface of the lake. The aim of this study is to analyze the spatiotemporal change of Lake Sevan surface water temperature based on remote sensing data and to analyze the relationship between the surface temperature of the lake water and the air temperature of the lake basin. The results confirm the relationship between the water surface temperature of Lake Sevan and the air temperature in the lake basin. Under conditions of reliability p
Keywords: Lake Sevan; water surface temperature; remote sensing data; air temperature